Building a sustainable future: conceptualizing the Sarawak Digital Community Center (DCC) development model - Wee, Chiat Lee; Azlina Bujang,; Sharin Sulaiman,; Siti Hafizah Ambi,; Adriana Amanda Nicholas, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This research paper endeavors to construct a comprehensive conceptual model for steering the sustainable evolution of Sarawak Digital Community Centers (SDCCs). The main emphasis is on figuring out crucial elements and procedures necessary for long-term sustainability and the constructive transformation of communities. The report examines the current state of Sarawak's Digital Community Centres in-depth and evaluates how they could support the Sustainable Development Goals (SDGs) listed in the 2030 Agenda for Sustainable Development of the United Nations. Three basic pillars—economic sustainability, environmental sustainability, and social sustainability—support our conceptual framework for sustainable development. Within this paradigm, we investigate the crucial functions played throughout the SDCC lifetime by governmental assistance, collaborative efforts, and technology innovation. To ensure relevance in a constantly changing digital environment, we also stress the crucial need of cybersecurity education and adaptability to emerging technology. Using a mixed-methods approach that combines thematic analysis and phone interviews, the Sarawak Digital Community Centres want to acquire insights into the strengths, weaknesses, opportunities, and dangers they are currently facing. The SWOT analysis framework draws on this assessment to generate its suggestions and policy directives for sustainable development. In conclusion, Sarawak's Digital Community Centres have enormous potential to strengthen local communities, promote inclusivity, and promote societal and economic growth. The suggested model offers stakeholders and policymakers a road map for strengthening SDCCs and maximizing their impact on sustainable community development in the age of the digital economy.